Global Inequality : From Class to Location, from Proletarians to Migrants - Milanovic, Branko (2012)
Inequality between world citizens in mid-19th century was such that at least a half of it could be explained by income differences between workers and capital-owners in individual countries. Real income of workers in most countries was similar and low. This was the basis on which Marxism built its universal appeal. More than 150 years later, in the early 21st century, the situation has changed fundamentally: more than 80 percent of global income differences is due to large gaps in mean incomes between countries, and unskilled workers' wages in rich and poor countries often differ by a factor of 10 to 1. This is the basis on which a new global political issue of migration has emerged because income differences between countries make individual gains from migration large. The key coming issue will be how to deal with this challenge while acknowledging that migration is probably the most powerful tool for reducing global poverty and inequality.